SCARCITY AS A MODERATOR OF DOUBLE DATE CAMPAIGNS AND FOMO ON PURCHASE INTENTION AMONG GEN Z SHOPEE USERS IN MALANG - Adinda Rizqy Amelia; Fani Firmansyah (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study explores how scarcity enhances the influence of double date campaigns and Fear of Missing Out (FOMO) on purchase intention among Generation Z Shopee users in Malang. Method: Employing a quantitative explanatory design with 155 respondents aged 18–28, an online survey was used to gather the data, and Partial Least Squares (PLS) was used for analysis via SmartPLS 4.0. Results: The results show that double date campaigns, FOMO, and scarcity significantly influence purchase intention. Furthermore, scarcity strengthens the effect of double date campaigns on purchase intention, but does not considerably reduce the association between purchase intention and FOMO. These results highlight the importance of combining time-limited promotions with psychological urgency strategies to optimize consumer responses in e-commerce marketing. Keywords: Double Date Campaign, Fear Of Missing Out, Generation Z, Purchase Intention, Scarcity